Mobile application development for CCTV system - Chen, Noel Yingsheng. (2013)
Analogue Closed Circuit Television (CCTV) systems have historically been deployed for security concerns. Internet Protocol (IP) CCTV cameras followed soon after, allowing CCTV footage to be viewed using a computer. With the advent of the mobile device age, current devices are capable of performing vast functions ranging from entertainment to communication purposes, packing the computational power required to perform audio and video media playback, Internet surfing and game playing.